An improved design of reversible adder/subtractor - P, Gowthami; V. S. Satyanarayana, R (International Journal of Engineering and Technology, 2018)
Reversible logic has gained an importance in the fields such as Quantum computing, DNA computing, Bio informatics, Nanotechnology and Optical computing etc. This paper presents a new design of reversible adder/subtractor circuit. The proposed design has better performance than the existing counterpart in terms of reversible gates, garbage outputs and quantum cost.Â